2015
DOI: 10.1080/15332691.2014.953657
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Impact of Technology on Couple Relationships: The Development of the Technology and Intimate Relationship Assessment

Abstract: The goal of this study was to develop an instrument to operationalize the impact of technology use on romantic relationship intimacy. The sample consisted of 241 undergraduate and graduate students who identified as being in a committed, monogamous intimate relationship. An exploratory factor analysis was conducted on an initial set of test items to reduce the number of items to those that explained the relationship between technology and romantic relationship intimacy. The factor structure and psychometric pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 31 publications
0
8
0
3
Order By: Relevance
“…32 Nonetheless, not all online interactions are detrimental to romantic relationships. 33,34 For example, Grov and colleagues 35 showed that moderate or light amounts of online sexual activities can yield relationship benefits, including increases in the quality and frequency of sex, and greater intimacy with the primary partner. This seems to depend on the agreements conveyed in the relationship and on what role technologymediated behaviors play in the relationship.…”
mentioning
confidence: 99%
“…32 Nonetheless, not all online interactions are detrimental to romantic relationships. 33,34 For example, Grov and colleagues 35 showed that moderate or light amounts of online sexual activities can yield relationship benefits, including increases in the quality and frequency of sex, and greater intimacy with the primary partner. This seems to depend on the agreements conveyed in the relationship and on what role technologymediated behaviors play in the relationship.…”
mentioning
confidence: 99%
“…Contestar el teléfono, interrumpir una conversación o contestar un mensaje frente a la pareja son situaciones que pueden tener significados diferentes para aquel que realiza la actividad y el que está co-presente. No obstante, los participantes en este estudio no reconocieron que su comunicación estuviera afectada, debido a que la tecnología forma parte de su cotidianidad (Campbell & Murray, 2015;Chotpitayasunondh & Douglas, 2018a).…”
Section: Discussionunclassified
“…Igualmente, no se obtuvo diferencias significativas en cuanto a nivel de escolaridad, hijos, tipo de relación, trabajo y religión. Sin embargo, se obtuvo diferencias por edades, los jóvenes emplean más estrategias negativas que los adultos mayores, lo que reafirma que en la conducta del phubbing existen diferencias generacionales, Además, de que reafirma que los jóvenes usan más la tecnología con sus parejas con mensajes más destructivos (Campbell & Murray, 2015), cuando se enfrentan a situaciones conflictivas. Esto es un tema que se requiere profundizar en futuros estudios.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Such technological advances have resulted in the rapid growth of Social Network Sites (SNSs) and have altered the manner in which one meets new people and establishes and maintains relationships (Day, 2013). Most individuals find the online setting for meeting others appealing, as it offers them the opportunity to meet individuals outside of their social circle, to meet individuals even with time limitations, and to meet and interact with others in a setting that is low-key and less anxiety-provoking (Campbell & Murray, 2015). Geographic mobility is typically one of the key reasons for friendships to dissolve, but, regardless of changes in physical proximity and the regularity of communication, individuals can maintain a form of intimacy with strong relationships which have a vast history of interaction (Shklovski, Kraut, & Cummings, 2008).…”
Section: Introductionmentioning
confidence: 99%